Genetic diversity of selected aromatic plants in Ayer Hitam Forest Reserve, Selangor - Mat Desa, Mohamad Azren Putra (2016)
Malaysia is rich in aromatic plant species but they have not been fully explored. During an exploration in October 2015 at Ayer Hitam Forest Reserve (AHFR), Selangor, several plant species were identified from their ability to produce strong aroma. They included Trema angustifolia (Cenderai/Mengkirai), Cinnamomum iners (Medang Teja), Actinodaphne sphaerocarpa (Medang Payung), Syzygium polyanthum (Serai Kayu), Prismatomeris glabra (Tongkat Haji Samad), Monocarpia marginalis (Mempisang) and Chromolaena odorata (Kapal Terbang). Morphology of each species was described and DNA samples were isolated to provide for genetic information. DNA samples were extracted using FavorPrep Plant Genomic DNA Extraction Mini Kit. The DNA psbA-trnH region was amplified in PCR and sequenced. Sequence analysis and searches data at GeneBank’s database revealed that many of Malaysian aromatic plant species have not been sequenced. This is the first report on genetic diversity of aromatic plants from AHFR. More efforts should be taken to document these plant species for potential use in producing aromatic-essential products.